An Evaluation of Alveolar Defects Using a Cone-Beam CT Scanner：A Clinical Study of Alveolar Height and Width on the Upper and Lower First Molars - UBUKATA, Masahito; ARAKI, Hisao; KAWABE, Yoshihiro; AMENOMORI, Hirotaka; MIZOBE, Kenichi (Journal of Japanese Society of Oral Implantology, 2012)
The purpose of the present study was to determine the rate of alveolar bone resorption in maxillary and mandibular edentulous regions assessed by cone-beam CT. The height and width of alveolar bone in the molar regions were respectively compared to the control edentulous sides. The subjects were 36 patients who were analyzed prior to dental implant surgery using a cone-beam CT scanner (XP62 Finecube, Yoshida Dental Manufacturing Co.) in standard imaging mode. To perform the measurements, a line was set perpendicular to the axis of the second premolar, and the measurement positions were set 5 mm distal to the intersection of alveolar bone margins from the distal surface of the second premolar. The height of alveolar bone was measured parallel to the axis of the second premolar, while the width was measured 1.5 mm basolateral to the alveolar bone crest. The study findings were as follows: (1) the height of upper alveolar bone on the edentulous side differed significantly from that on the control side (p＜0.05), and the bone resorption rate was 27%; (2) the width of upper alveolar bone on the edentulous side was significantly different from that on the control side (p＜0.05), and the bone resorption rate was 33%; (3) the height of lower alveolar bone on the edentulous side did not differ significantly from that on the control side, and the bone resorption rate was 5%; (4) the width of lower alveolar bone on the edentulous side was significantly different from that on the control side (p＜0.05), and the bone resorption rate was 32%; (5) comparisons of upper and lower alveolar bone height revealed that lower alveolar bone was significantly larger than upper alveolar bone on both the edentulous side and the control side. These findings demonstrate that the height of lower alveolar bone hardly changed even if teeth were missing. However, the height of upper alveolar bone, the width of upper alveolar bone and the width of lower alveolar bone become smaller due to missing teeth.